Non-specialization of criminal careers among intimate partner violence offenders - Hilton, N. Zoe (Criminal justice and behavior, 2016)
Many men arrested for intimate partner violence (IPV) commit other types of criminal offenses as well. We examined 93 IPV offenders? general offending and tested the ability of criminal career trajectory and an IPV-specific risk assessment (Ontario Domestic Assault Risk Assessment [ODARA]) to predict post-index recidivism 7.5 years later. Most (71%) had pre-index criminal charges, and most (62%) had post-index criminal recidivism, although fewer (24%) committed post-index IPV. Pre-index criminal career (defined as none, non-violent, violent, IPV) did not predict post-index IPV, whereas the ODARA predicted post-index IPV, area under the curve (AUC = .67), as well as other offenses with a moderate or large effect size, including stalking (AUC = .78), sexual assault (AUC = .67), and non-violent offenses (AUC = .74). In line with prior research findings, we conclude that many men arrested for IPV do not specialize in their criminal careers and that risk assessment in these cases could include risk of both IPV and other offenses. Furthermore, the ODARA holds promise for assessing general risk of recidivism among IPV offenders.